Celestial bodies : a novel - Ḥārithī, Jūkhah (Catapult, 2019)
In the village of al-Awafi in Oman, we encounter three sisters: Mayya, who marries after a heartbreak; Asma, who marries from a sense of duty; and Khawla, who chooses to refuse all offers and await a reunion with the man she loves, who has emigrated to Canada. These three women and their families, their losses and loves, unspool beautifully against a backdrop of a rapidly changing Oman, a country evolving from a traditional, slave-owning society into its complex present. Through the sisters, we glimpse a society in all its degrees, from the very poorest of the local slave families to those making money through the advent of new wealth. The first novel originally written in Arabic to ever win the Man Booker International Prize, and the first book by a female Omani author to be translated into English, Celestial Bodies marks the arrival in the United States of a major international writer.